Brewer's dictionary of phrase and fable - Brewer, Ebenezer Cobham, 1810-1897 (Harper & Row, 1981)
Brewer's Dictionary of Phrase and Fable takes you on a captivating adventure through its trademark blend of language, culture, myth and legend. As Susie Dent explains in the foreword, Brewer's 'is not a straightforward dictionary, nor is it an encyclopaedia. It is, in fact, unlike any other reference book that exists, anywhere.' This 19th edition encapsulates all the charm and wit that characterise its predecessors and maintains the standards of scholarship and eclecticism that have long been its hallmark.